2011
DOI: 10.1002/prot.23217
|View full text |Cite
|
Sign up to set email alerts
|

Structural and binding studies of the C‐terminal domains of yeast TFIIF subunits Tfg1 and Tfg2

Abstract: The general transcription factor TFIIF plays essential roles at several steps during eukaryotic transcription. While several studies have offered insights into the structure/function relationship in human TFIIF, much less is known about the yeast system. Here, we describe the first NMR structural and binding studies of the C-terminal domains (CTDs) of Tfg1 and Tfg2 subunits of Saccharomyces cerevisiae TFIIF. We used the program CS-ROSETTA to determine the three-dimensional folds of these domains in solution, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 48 publications
(155 reference statements)
0
2
0
Order By: Relevance
“…The present results may also provide fundamental insight into the biological function and mechanism of WH domains for regulating cellular processes and, in particular transcription, via protein–protein interactions. Intriguingly, although early studies suggested that the C-terminal WH domain of RAP74 may not bind DNA, a very recent study demonstrated that the yeast homologue binds nonspecific DNA with modest affinity . Moreover, although early studies suggested that WH domains primarily function in binding DNA, several studies have now demonstrated that WH and similar domains can also function in protein–protein interactions. ,,,,, In particular, kinetic studies have suggested that the disordered Activation Factor 1 (AF1) of the Androgen Receptor (AR) also binds the same hydrophobic cleft of the RAP74 WH domain .…”
Section: Discussion and Conclusionmentioning
confidence: 99%
“…The present results may also provide fundamental insight into the biological function and mechanism of WH domains for regulating cellular processes and, in particular transcription, via protein–protein interactions. Intriguingly, although early studies suggested that the C-terminal WH domain of RAP74 may not bind DNA, a very recent study demonstrated that the yeast homologue binds nonspecific DNA with modest affinity . Moreover, although early studies suggested that WH domains primarily function in binding DNA, several studies have now demonstrated that WH and similar domains can also function in protein–protein interactions. ,,,,, In particular, kinetic studies have suggested that the disordered Activation Factor 1 (AF1) of the Androgen Receptor (AR) also binds the same hydrophobic cleft of the RAP74 WH domain .…”
Section: Discussion and Conclusionmentioning
confidence: 99%
“…The chemical shifts were previously obtained by Kilpatrick et al from HNCACB and CBCA(CO)NH experiments, and manually assigned to 99% completeness. 23 The chemical shift dataset was divided into sub-sections, randomized, and used for algorithmic analysis.…”
Section: Resultsmentioning
confidence: 99%